TEKNIK GRAFT SEDERHANA PADA KULIT (Media Dermato Venereologica Indonesiana, 2020)
Graft is the skin transplantation from donor site to recipient site with nutrients obtained from the recipient's wound bed. Skin graft can be classified according to donor origin, histology, differences in thickness, and shape. Simple graft techniques such as full-thickness skin grafts (FTSG), split-thickness (STSG) skin grafts, and epidermal grafts (EG) are important knowledge in the dermatologic practice. The FTSG, skin layer consists of all layers of the epidermis and dermis, STSG consists of layers of skin and partial of dermis with or without hair follicles, whereas EG only contains layers of the epidermis. Indications of skin graft include post-removal of skin malignancies, chronic ulcers, burns, and vitiligo. The process of wound healing in grafts is different from conventional wounds. Five important phases in wound helaing are imbibition serum, inosculation, revascularization, innervation, and maturation. There are various conditions for donors and recipients that must be considered before grafting. Many factors contribute to the success of graft, including stabilization and compression of graft during the process of revascularization. Post-graft complications management is also essential knowledge in the holistic approach performing graft technique.